Anterior Thigh Pain Following Minimally Invasive Oblique Lateral Interbody Fusion: Multivariate Analysis from a Prospective Case Series - Chang, Sam Yeol; Lee, Woo Seok; Mok, Sujung; Park, Sung Cheol; Kim, Hyoungmin; Chang, Bong-Soon (Clinics in orthopedic surgery, 2022)
Oblique lateral interbody fusion (OLIF) involves the antepsoas approach and psoas major muscle (PMM) retraction to insert the interbody cage orthogonally. Therefore, OLIF is often associated with postoperative anterior thigh pain (ATP) on the approach side. However, there is limited evidence on the nature and risk factors of ATP following OLIF.BackgroundOblique lateral interbody fusion (OLIF) involves the antepsoas approach and psoas major muscle (PMM) retraction to insert the interbody cage orthogonally. Therefore, OLIF is often associated with postoperative anterior thigh pain (ATP) on the approach side. However, there is limited evidence on the nature and risk factors of ATP following OLIF.Consecutive patients who planned to undergo minimally invasive OLIF and percutaneous pedicle screw instrumentation for lumbar degenerative diseases were prospectively enrolled. The visual analog scale (VAS) for ATP was recorded, and a pain map was drawn daily from the operation day to postoperative day 7 in all patients. We also prospectively collected the preoperative and intraoperative data to identify the risk factors associated with ATP. Radiologically, the total cross-sectional area (CSA), retraction length, and retraction CSA of PMM were measured from the preoperative T2-weighted axial magnetic resonance imaging scans at the L4-5 intervertebral disc level. The patients were stratified into two groups based on the experience of ATP with a VAS score of ≥ 7 at any time point. Additionally, a binary logistic regression analysis was performed to identify the associated factors.MethodsConsecutive patients who planned to undergo minimally invasive OLIF and percutaneous pedicle screw instrumentation for lumbar degenerative diseases were prospectively enrolled. The visual analog scale (VAS) for ATP was recorded, and a pain map was drawn daily from the operation day to postoperative day 7 in all patients. We also prospectively collected the preoperative and intraoperative data to identify the risk factors associated with ATP. Radiologically, the total cross-sectional area (CSA), retraction length, and retraction CSA of PMM were measured from the preoperative T2-weighted axial magnetic resonance imaging scans at the L4-5 intervertebral disc level. The patients were stratified into two groups based on the experience of ATP with a VAS score of ≥ 7 at any time point. Additionally, a binary logistic regression analysis was performed to identify the associated factors.The current prospective study included 92 patients (31 men, 61 women) with a mean age of 70.4 years (range, 56-86 years), who underwent OLIF at our institution. The left-side approach was used in 73 patients (79.3%), while 19 (20.7%) underwent a right-side approach. Sixty-five of the total patients (70.6%) experienced approach-side ATP to any extent during postoperative 0-7 days following OLIF. The mean pain VAS (4.4 ± 2.1) and the prevalence (57.6%) were highest at postoperative 2 days. On postoperative day 7, there were 19 patients (20.7%) who complained of residual ATP with a mean VAS of 2.6 ± 1.8. In the multivariate analysis, the PMM retraction length was significantly associated with ATP of VAS ≥ 7 (adjusted odds ratio, 2.316; p = 0.044).ResultsThe current prospective study included 92 patients (31 men, 61 women) with a mean age of 70.4 years (range, 56-86 years), who underwent OLIF at our institution. The left-side approach was used in 73 patients (79.3%), while 19 (20.7%) underwent a right-side approach. Sixty-five of the total patients (70.6%) experienced approach-side ATP to any extent during postoperative 0-7 days following OLIF. The mean pain VAS (4.4 ± 2.1) and the prevalence (57.6%) were highest at postoperative 2 days. On postoperative day 7, there were 19 patients (20.7%) who complained of residual ATP with a mean VAS of 2.6 ± 1.8. In the multivariate analysis, the PMM retraction length was significantly associated with ATP of VAS ≥ 7 (adjusted odds ratio, 2.316; p = 0.044).In this study, we prospectively collected and analyzed the ATP and associated factors following OLIF and identified the PMM retraction length as a potential independent risk factor for severe ATP in the immediate postoperative period following OLIF. Keywords: Anterior thigh pain, Psoas major muscle, Antepsoas, Oblique lateral interbody fusion, Genitofemoral nerve.ConclusionsIn this study, we prospectively collected and analyzed the ATP and associated factors following OLIF and identified the PMM retraction length as a potential independent risk factor for severe ATP in the immediate postoperative period following OLIF. Keywords: Anterior thigh pain, Psoas major muscle, Antepsoas, Oblique lateral interbody fusion, Genitofemoral nerve.